Ubiquity and Diversity of Cold Adapted Denitrifying Bacteria Isolated From Diverse Antarctic Ecosystems - Cabezas, Angela; Azziz, Gastón; Bovio-Winkler, Patricia; Fuentes, Laura; Braga, Lucía; Wenzel, Jorge; Sabaris, Silvia; Tarlera, Silvana; Etchebehere, Claudia (Frontiers in Microbiology, 2022)
Nitrogen cycle has been poorly investigated in Antarctic ecosystems. In particular, how extreme conditions of low temperature, dryness, and high radiation select the microorganisms involved in the cycle is not yet understood. Denitrification is an important step in the nitrogen cycle in which nitrate is reduced stepwise to the gases NO, N2O, and N2. Denitrification is carried out by a wide group of microorganisms spread in the phylogenetic tree. The aim of this work was to isolate and characterize denitrifying bacteria present in different cold environments from Antarctica. Bacterial isolates were obtained from lake, meltwater, sea, glacier ice, ornithogenic soil, and penguin feces samples from King George Island, Fildes peninsula in the Antarctic. Samples were taken during the deicing season in five sampling campaigns. From all the samples we were able to isolate denitrifying strains. A total of 199 bacterial isolates with the capacity to grow in anaerobic mineral media reducing nitrate at 4°C were obtained. The characterization of the isolates by 16S rRNA gene sequence analysis showed a high predominance of the genus Pseudomonas, followed by Janthinobacterium, Flavobacterium, Psychrobacter, and Yersinia. Other minor genera detected were Cryobacterium, Iodobacter, Kaistella, and Carnobacterium. The capacity to denitrify was not previously described for most of the bacteria related to our isolates and in many of them denitrifying genes were not present suggesting the presence of new genes in this extreme environment. Our work demonstrates the ubiquity of denitrification in the Maritime Antarctica and gives important information linking denitrification at cold temperature with taxa in an unequivocal way.